Évolutions de la formation initiale des enseignants : entre logique managériale gestionnaire et vécu des pilotes-formateurs - Thérèse Perez-Roux; Eric Maleyrot (Éducation et Socialisation)
This paper examines changes in initial teacher training in France, based on the institutional discourse that has underpinned successive reforms since the creation of university teacher training institutes in 1990. Using a sociological approach, the article looks at how the 2019 reform reconfigures the issues of professionalisation and universitisation of training by examining the managerial rationales at work. An analysis of the discourses of training managers (trainers with a steering function) reveals a number of indicators of an instrumentalist approach to new public management. Constrained timeframes and difficulty in planning ahead, worsening working conditions due to economic considerations, the loss of collectives and increased flexibility on the part of trainers all seem to be part of a perspective of managerial and financial control, far removed from what prevailed when the university teacher training institutes were created.